Keefektifan Teknik Sosiodrama Untuk Mengurangi Perilaku Bullying Verbal Kelas VIII di SMP Negeri 1 Glenmore - Handoko, Adista Desintasari; Rahmawati, Weni Kunia; Mawaddati, Ika Romika (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2024)
Bullying is an issue that often arises among teenagers, both in school environments and within the community. Reducing bullying behavior can be achieved using sociodrama. This research aims to reduce students' verbal bullying behavior using sociodrama techniques. This sociodrama technique is helpful in reducing bullying behavior through role-playing. The approach used in this study is a quantitative research type with a pre-experimental design method using a one-group pre-test design. Data analysis in this study uses the Wilcoxon test, aided by SPSS for Windows version 22. Based on the data analysis results using SPSS 22 software, it was found that sociodrama techniques effectively reduce verbal bullying behavior among eighth-grade students at SMPN 1 Glenmore.